Wavelet Transform-Based UV Spectroscopy for Pharmaceutical Analysis - Dinç, Erdal; Yazan, Zehra (Frontiers in Chemistry, 2018)
In research and development laboratories, chemical or pharmaceutical analysis has been carried out by evaluating sample signals obtained from instruments. However, the qualitative and quantitative determination based on raw signals may not be always possible due to sample complexity. In such cases, there is a need for powerful signal processing methodologies that can effectively process raw signals to get correct results. Wavelet transform is one of the most indispensable and popular signal processing methods currently used for noise removal, background correction, differentiation, data smoothing and filtering, data compression and separation of overlapping signals etc. This review article describes the theoretical aspects of wavelet transform (i.e. discrete, continuous and fractional) and its characteristic applications in UV spectroscopic analysis of pharmaceuticals.